A STUDY ON THE DISTRIBUTION AND ABUNDANCE OF NORMAL FLORA ON THE HUMAN SKIN AND ITS RELATIONSHIP TO THE USE AND NON-USE OF COSMETICS - Varghese, L S; Sajeevkumar, A; Muralidahran, A V; Paul, K J; Viswanathan, S (International Journal of Ayurveda and Pharma Research, 2015)
The long term use of cosmetics modifies the microbial ecology on the skin surface. The present study quantitatively assayed the microbial flora on female respondents (age group of 18-20 yrs) using and not using cosmetics, plus those who use coconut oil alone on the skin surface. The results showed that the higher number of microbial flora is observed on skin surface of respondents using coconut oil (90.4 x 102 cfu/ 5 cm2 skinarea). The microbial count of respondents using and not using cosmetics were 34.4 x102 and 45.6 x102 cfu, respectively, per 5 cm2 area of skin surface. Cosmetics (C1 to C6) were assayed for antibacterial activity where C1, C2, C3, C4 and C6 were resistant to the three species of test bacteria namely Staphylococcus aureus, Coagulase negative Staphylococcus and E. coli. The sample C5 exhibited a low level of antibacterial activity against E. coli with a diameter of zone of growth inhibition of 9 mm. An assay carried out for a period of six months to compare the modifying effect of cosmetics on skin microflora of a respondent whose left hand was applied with a body lotion (C7) and her right hand not applied with any topical applicants. There was reduction in the number of microflora on the left hand with an average count of 13.3 x 102 cfu/ 5 cm2 area on the skin surface, than on the right hand with an average count of 22.6 x 102 cfu/ 5 cm2 area on the skin surface.